Design, Synthesis, Biological Evaluation, and Molecular Modeling of Coumarin–Piperazine Derivatives as Acetylcholinesterase Inhibitors. Issue 11 (8th October 2013) - Modh, Rahul P.; Kumar, Sivakumar Prasanth; Jasrai, Yogesh T.; Chikhalia, Kishor H.
<x xml:space="preserve">Abstract</x> Acetylcholinesterase (AChE) is an important drug target for the treatment of Alzheimer's disease. A novel series of coumarin–piperazine derivatives were synthesized and their potency to inhibit human AChE enzyme (hAChE) was studied. All the final compounds were characterized by infrared, 1H NMR, 13C NMR, and elemental analysis. Docking experiments of the designed coumarin–piperazine derivatives were carried out in order to compare the theoretical and experimental binding affinities toward hAChE, to delineate the inhibitory mechanism. Subsequently, a structure–activity relationship (SAR) study using the molecular field method showed that the hydrophobic field and positive charge center conferred by the coumarin and piperazine moieties demonstrated an inhibitory mechanism. Among the compounds tested, 3f, 3j, and 3m were found to be the most potent inhibitors of hAChE.